Coaching implications of the lateral batting backlift technique in men's cricket: a discussion and food for thought. Issue 1 (17th March 2019) - Noorbhai, Habib; Noakes, Timothy
Abstract : Cricket coaching manuals published after 2009 accept as a norm for batsmen to lift the bat in the direction of the slips. A mixed-methods study conducted among 161 coaches around the world showed that most cricket coaches (83%) coach the straight batting backlift technique (SBBT) as opposed to the lateral batting backlift technique (LBBT) at various proficiency levels of the game. The LBBT (more beneficial for cricket batsmen) is one in which the bat is lifted laterally in the direction of second slip or gully. Using this technique, the face of the bat faces towards point or the off-side. In contrast, the backlift in which the bat is lifted towards the stumps or first slip and the face of the bat points towards the wicket-keeper or the ground, is known as the SBBT. This paper attempts to provide implications for coaching the LBBT and understanding some important aspects of cricket batsmanship in men's cricket.